Association of serum, follicular fluid, and embryo culture media homocysteine levels with embryo quality and pregnancy rates in assisted reproductive techniques - Xuxin Zhan; Xiaoting Wang; Jinxia Xie; Jing Zhao; Hongli Zhu (Medicine, 2026)
Homocysteine (Hcy) is involved in reproductive metabolism, but the associations of Hcy levels in different reproductive microenvironments with embryo development and pregnancy outcomes remain unclear. This study investigated these associations in women undergoing in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI). This prospective study included 66 women undergoing IVF/ICSI treatment. Serum and follicular fluid (FF) samples were collected on the day of oocyte pick-up, and Hcy concentrations were measured using an enzyme cycling assay. Hcy levels in discarded embryo culture media collected on day 3 were also determined. Spearman correlation analysis was performed to assess the relationships among Hcy levels in different biological compartments. Multivariable linear and logistic regression models were used to evaluate the associations of Hcy concentrations with embryological outcomes and clinical pregnancy outcomes after adjustment for potential confounding factors. Serum Hcy levels were weakly positively correlated with FF Hcy concentrations (rs = 0.302, P = .014), whereas embryo culture medium Hcy levels were not significantly correlated with either serum or FF Hcy levels. After adjustment for female age, body mass index, total gonadotropin dose, and basal follicle-stimulating hormone levels, higher embryo culture medium Hcy levels were significantly associated with a lower blastocyst formation rate (β = −20.53, 95% CI: −38.07 to − 2.98; P = .025). In the analysis of clinical pregnancy outcomes, serum Hcy levels were not significantly associated with clinical pregnancy. After adjustment for female age and body mass index, intermediate FF Hcy levels were associated with a higher likelihood of clinical pregnancy, whereas no significant association was observed for the highest Hcy level group. In addition, compared with the intermediate Hcy level group, the highest embryo culture medium Hcy level group was associated with clinical pregnancy outcomes. Hcy levels in different reproductive microenvironments exhibited distinct associations with embryo development and clinical pregnancy outcomes. Compared with serum Hcy, Hcy levels in FF and embryo culture medium may provide complementary information for evaluating embryonic developmental potential and reproductive outcomes during IVF/ICSI. Further large-scale prospective studies are warranted to validate these findings.